2018
DOI: 10.1017/s1368980018002859
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating interventions to improve child nutrition in Eastern Democratic Republic of Congo

Abstract: ObjectiveThe prevention of malnutrition in children under two approach (PM2A), women’s empowerment and agricultural interventions have not been widely evaluated in relation to child diet and nutrition outcomes. The present study evaluated the effectiveness of PM2A, women’s empowerment groups (WEG), farmer field schools (FFS) and farmer-to-farmer training (F2F).DesignCommunity-matched quasi-experimental design; outcome measures included children’s dietary diversity, stunting and underweight.SettingCommunities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The extremely resource-limited context may have been an important factor contributing to the contrary findings. The results of the parent study found that stunting prevalence ranged from 55 to 70% among children in intervention group households and 47% of households were severely food insecure at endline, making this a particularly nutritionally deprived group [30,48]. In such a food insecure environment, opportunities to improve dietary diversity are limited, and differences in dietary diversity among participants with higher levels of mental health symptoms compared to those with less severe symptoms may be due to other underlying or modifying factors, such as social support and work burden.…”
Section: Discussionmentioning
confidence: 99%
“…The extremely resource-limited context may have been an important factor contributing to the contrary findings. The results of the parent study found that stunting prevalence ranged from 55 to 70% among children in intervention group households and 47% of households were severely food insecure at endline, making this a particularly nutritionally deprived group [30,48]. In such a food insecure environment, opportunities to improve dietary diversity are limited, and differences in dietary diversity among participants with higher levels of mental health symptoms compared to those with less severe symptoms may be due to other underlying or modifying factors, such as social support and work burden.…”
Section: Discussionmentioning
confidence: 99%
“…Additional findings, including a comparison of all interventions, are presented elsewhere, along with more detailed information about overall study methods and statistical analyses. 19 , 20 Here we summarize the methods relevant to the current research, as well as information specific to the FFS analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Data were collected in 8 semiannual surveys (August/September and February/March) to account for seasonal variations in food security. 20 Both data collection periods were at the beginning of local rainy seasons. 21…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations